2005
DOI: 10.1055/s-2005-918493
|View full text |Cite
|
Sign up to set email alerts
|

Electroorganic Synthesis of 2,5-Dialkoxydihydrofurans and Pyridazines on Solid Phase Using Polymer Beads as Supports

Abstract: Electroorganic synthesis has defied application in SolidPhase Organic Synthesis (SPOS) so far. Typically more than 99.9% of the substrate molecules immobilized on a polymeric support are buried in the interior of the bead, and therefore are unable to undergo direct contact with a heterogeneous reagent such as an electrode. This intrinsic impediment for an electrochemical reaction can be overcome by the use of a redox mediator which shuttles electrons from the electrode to the polymer bound substrate molecules.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this report, we demonstrated that furans are viable substrates in nickel‐catalyzed electrohomocouplings, despite their high reactivity in oxidative processes such as in anodic methoxylations, cyanations, and polymerizations [74–82] . The developed method could be applied to the synthesis of both 2,2′‐bifuran‐5,5′‐dicarboxylic acid dimethyl ester and 3,3′‐bifuran‐5,5′‐dicarboxylic acid dimethyl ester, which are key constituents in highly potential bio‐based bifuran polymers and bifuran‐furan co ‐polymers [28–30] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this report, we demonstrated that furans are viable substrates in nickel‐catalyzed electrohomocouplings, despite their high reactivity in oxidative processes such as in anodic methoxylations, cyanations, and polymerizations [74–82] . The developed method could be applied to the synthesis of both 2,2′‐bifuran‐5,5′‐dicarboxylic acid dimethyl ester and 3,3′‐bifuran‐5,5′‐dicarboxylic acid dimethyl ester, which are key constituents in highly potential bio‐based bifuran polymers and bifuran‐furan co ‐polymers [28–30] .…”
Section: Discussionmentioning
confidence: 97%
“…In this report, we demonstrated that furans are viable substrates in nickel-catalyzed electrohomocouplings, despite their high reactivity in oxidative such as in anodic methoxylations, cyanations, and polymerizations. [74][75][76][77][78][79][80][81][82] The developed method could be applied to the synthesis of both 2,2'-bifuran-5,5'-dicarboxylic acid dimethyl ester and 3,3'-bifuran-5,5'-dicarboxylic acid dimethyl ester, which are key constituents in highly potential bio-based bifuran polymers and bifuran-furan copolymers. [28][29][30] Importantly, the electrolysis can be performed in the absence of sacrificial anodes, and the products can be recovered without chromatography by precipitation, which might facilitate the upscaling of the reaction.…”
Section: Discussionmentioning
confidence: 99%